The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/liv.15270
|View full text |Cite
|
Sign up to set email alerts
|

An MMP‐degraded and cross‐linked fragment of type III collagen as a non‐invasive biomarker of hepatic fibrosis resolution

Abstract: Background and Aims Liver fibrosis results from a prolonged wound healing response to continued injury with excessive production of extracellular proteins. In patients with chronic liver disease, the monitoring of liver fibrosis dynamics is of high interest. Whilst markers of fibrogenesis exist, markers of hepatic fibrosis resolution remain an unmet clinical need. Thus, we sought to develop an assay quantifying a circulating proteolytic fragment of cross‐linked type III collagen as a biomarker of fibrolysis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Our data demonstrated elevated fibrolysis in patients with a ‘severe fibrotic endotype,’ indicating an increased turnover of mature cross-linked type III collagen potentially due to excessive collagen deposition. Previous data of CTX-III in hepatitis C-associated liver fibrosis demonstrated a correlation of this biomarker with regressive liver fibrosis [ 39 ]. Patients with severe fibrosis could achieve fibrosis regression due to the resolution of the fibrotic extracellular matrix resulting from the high turnover indicated by elevated serum CTX-III.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrated elevated fibrolysis in patients with a ‘severe fibrotic endotype,’ indicating an increased turnover of mature cross-linked type III collagen potentially due to excessive collagen deposition. Previous data of CTX-III in hepatitis C-associated liver fibrosis demonstrated a correlation of this biomarker with regressive liver fibrosis [ 39 ]. Patients with severe fibrosis could achieve fibrosis regression due to the resolution of the fibrotic extracellular matrix resulting from the high turnover indicated by elevated serum CTX-III.…”
Section: Discussionmentioning
confidence: 99%
“…The primary impurities detected in recombinant IgG include a single light chain (LC), a combination of two heavy chains and one light chain (2H1L), two heavy chains (2H), and nonglycosylated IgG. In recent experiments conducted in our laboratory, we observed a significant disparity when exchanging a monoclonal antibody directed towards CTX-III [14] from hybridoma to recombinant antibody, despite their identical amino acid sequences. We found that the recombinant antibody led to substantially lower sensitivity and maximal signals in the CTX-III assay when compared to the hybridoma antibody (as illustrated in Table 2).…”
Section: Antibodiesmentioning
confidence: 99%
“…Type III collagen is primarily derived from activated fibroblasts and increased formation has been shown for CAFs [ 31 , 32 ]. The increased expression, maturation, and remodeling of type III collagen have been associated with cancer and multiple fibrotic disorders [ 31 , 33 , 34 , 35 ]. Multiple MMPs have been shown to cleave native type III collagen including MMP-1, MMP-8, MMP-9, MMP-12, and MMP-13 [ 33 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increased expression, maturation, and remodeling of type III collagen have been associated with cancer and multiple fibrotic disorders [ 31 , 33 , 34 , 35 ]. Multiple MMPs have been shown to cleave native type III collagen including MMP-1, MMP-8, MMP-9, MMP-12, and MMP-13 [ 33 , 36 , 37 , 38 ]. Zhang et al have investigated FAP cleavage in the ECM using degradomics based on terminal amine isotopic labelling of substrates (TAILS) in mice and identified novel cleavage sites that could potentially be used to reflect FAP activity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%